POLA PERGERAKAN KSPPS CITRA ARTHA MANDIRI BREBES (DAMPAK COVID-19) - Mohamad Yamin; Ismawan Khoeruman Azam (IAIC (Institut Agama Islam Cirebon), 2022)
The Covid-19 pandemic is one of the viruses that has hit Indonesia since March 2020, which has resulted in thousands of Indonesians experiencing serious illness, even leading to death and very high economic losses. The Covid-19 pandemic has caused an increase in unemployment and a decline in the community's economy caused by the cessation of business activities. This study aims to determine the impact of the Covid-19 pandemic on KSPSS Citra Artha Mandiri Brebes. This studyuses a qualitative descriptive method with anursing process approach or nursing process which aims to understand the object under study and to explain how the existence and how many cases occurred.